LGBTQ Health Surveillance: Data = Power - Sell, Randall L. (American journal of public health (1971))
The few pioneering sexual and gender minority health researchers were attempting to study the health of these populations in the 1980s without any significant funding or access to government-controlled data sources and surveillance systems. [...]yes, the National Health Interview Survey has started to collect sexual orientation data, allowing researchers to report cancer-related behaviors among lesbians as I requested so long ago.1 Unfortunately, only a tiny fraction of surveys used to monitor the health of the US population currently collect sexual orientation data, and an even smaller number collect gender identity data.2 Furthermore, because of the lack of guidance on the collection of these data, there are notable differences between surveys in the questions used to assess these constructs. At some point, the secretary of Health and Human Services needs to require the collection of sexual orientation and gender identity data in every survey they have jurisdiction over, just as a previous secretary required for race and ethnicity. [...]knowing LGBTQ (lesbian, gay, bisexual, transgender, and queer or questioning) people and their history, I know that the more impossible a challenge seems, the more likely they are to stand up and fight. Gonzales G, Przedworski J, HenningSmith C. Comparison ofhealth and health risk factors between lesbian, gay, and bisexual adults and heterosexual adults in the United States: results from the National Health Interview Survey. Correspondence should be sent to Randall L. Sell, ScD, MA, MS, Associate Professor, Dornsife School of Public Health, Department of Community Health and Prevention, 3215 Market Street, Room...